Nucleotide-directed syntheses of gold nanohybrid systems with structure-dependent optical features Selective fluorescence sensing of Fe3+ ions - Ungor Ditta Anita (COLLOIDS AND SURFACES B: BIOINTERFACES, 2017)
Abstract This study demonstrates a one-step synthesis for the preparation of both adenosine monophosphate (AMP)-stabilized colloidal gold nanoparticles (AMP-Au NPs) and fluorescent gold nanoclusters (AMP-Au NCs). The dominant role of AMP:AuCl4− molar ratios in the formation of diverse nanosized Au products was proved. The size, the structure and the unique structure-dependent optical properties of the NPs and NCs were determined based on the results of numerous spectroscopic (UV–vis, fluorescence, infrared, x-ray photoelectron), high resolution electron microscopy (HRTEM) and dynamic light scattering (DLS) techniques. Stabile AMP-Au NPs with diameter of ca. 11 nm and ultra-small AMP-Au NCs having blue fluorescence (λem = 480 nm) were identified. In addition, the AMP-Au NCs have been utilized to develop a selective sensor for the detection of Fe3+ ions in aqueous medium based on fluorescence quenching. Several essential metal ions and anions have been tested but our results clearly supported that dominant quenching was observed only for Fe3+ ions. Based on the determined limit of detection (LOD = 2.0 μM) our system is capable of detecting Fe3+ ions in drinking water. The Stern-Volmer constants (KSV) and various thermodynamic parameters (ΔG, ΔH°, ΔS°, ΔCp) of the quenching process have also been determined by the Stern-Volmer fitting of the fluorescence data in order to better understand the quenching mechanism.